The Effect of Vocabulary and Phonological Awareness on Students’ Reading Comprehension - Purwati, Heni (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
The purpose of this research was to investigate the effect of vocabulary and phonological awareness on students’ reading comprehension. This research was mainly quantitative in nature. The sample of this research was the tenth-grade students of SMK YPKP SENTANI. It consisted of 93 students assigned using random sampling technique. Vocabulary, phonology and reading comprehension tests were used as the instruments to collect the data. Then, the data were processed using regression analysis to figure out the effect of vocabulary and phonological awareness on reading comprehension. In the regression analysis using SPSS program, the data were entered into variable boxes. Vocabulary and phonological awareness scores were entered into independent variable box while scores of reading comprehension were entered into dependent variable box. The findings revealed that the regression value of vocabulary and phonological awareness on reading comprehension was significant. Furthermore, vocabulary and phonological awareness contributed 67.6% of effect on students’ reading comprehension. In addition, the finding of each variable showed that significant value of phonological awareness was higher than vocabulary. This result showed that the effect of phonological awareness was 64.5%, while the effect vocabulary was 31.2% on reading comprehension based on the Pearson Product Moment correlation.